URGENSI AMANDEMEN UNDANG UNDANG PERKOPERASIAN - WIDIASTUTI - (Wacana Hukum, 2009)
Abstract: The phenomenon in empirical domain of saving and credit cooperation is believed to have destroyed the ideal concept of cooperation. However, the norms can not protect the concept. Saving and credits are often used by the managerial, mostly businessmen to offer saving and draw credits from the society. The unbalance of of the contributed capital and the authority of drawing credit risks in the security of the creditors. The lack of the rules in cooperation Rules about if unmet of formal requirements causes the managerial to take the responsibility personally gives a lot of advantages to the managerial. It is because the managerial conduct cooperation as a firm with a very limited responsibility. Keywords: cooperation, changes of cooperation rules